Site Visits and Corporate Investment Efficiency - Cao, Sean Shun; Gong, Guojin; Kim, Yongtae; Shi, Hanzhong; Wang, Angie (Management Science, 2024)
Site visits allow visitors to physically inspect productive resources and interact with on-site employees and executives face to face. We posit that, by allowing visitors to acquire investment-related information and monitor the management team, site visits offer disciplinary benefits for corporate investments. Using mandatory disclosures of site visits in China, we find that corporate investments become more responsive to growth opportunities as the intensity of site visits increases, consistent with the notion that site visits yield disciplinary benefits. We also find that the positive association between site visits and investment efficiency is more pronounced when visitors can glean more investment-related information and when they have stronger incentives and greater power to monitor managers. This positive association is also stronger among firms with more severe agency problems and higher asset tangibility. The overall evidence supports the notion that site visits serve as a unique venue for institutional investors and financial analysts to acquire valuable information and serve a monitoring function, which generates disciplinary benefits for corporate investments. This paper was accepted by Suraj Srinivasan, accounting. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.00302 .